STUDI BANDING MANAJEMEN KANDANG RAWAT INAP ANJING SAKIT DI LABORATORIUM KLINIK HEWAN JOGJA DAN RSH. PROF SOEPARWI YOGYAKARTA - , SIGIT RAHARJO, Drh.Sudarminto. M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Cage is home to an animal that serves to protect the animals from harassment and threats from outside sehinnga animal will feel safe. Appropriate cage management will maximize the function of the enclosure as a protected animal. The practice of field work aimed to investigate the management inpatient sick dog cage that was conducted on 14 to 20 April 2014 to the Laboratory Animal Clinic Jogja Pamularsih Road No 55 Klaseman Condongcatur, Depok, Sleman, Jogjakarta and May 16, 2014 to Prof. Animal Hospitals Soeparwi Yacaranda Road, Unit II Sekip Yogyakarta. The purpose of this thesis is to investigate the management of a dog cage inpatient hospital in Yogyakarta Animal Clinic and Animal Hospital Prof Soeparwi. The method used in the search of data required for the compilation of the final task is done by direct observation of the enclosure, the enclosure measurement and dialogue with the person in charge of Jogja Animal Clinic and Animal Hospital Assoc Soeparwi. Management of inpatient sick dog cage done by cleaning with detergent cage once a day in the morning at 07.00. Disinfectant used to shed inpatient TH4+ dog is sick. Pens inpatient sick dog at Animal Hospitals Prof Soeparwi more organized because of hospitalization separated cages cat while in Jogja Animal Clinic kennel and the cat is still in a room due to space inpatient pain is still in the development stage, The conclusion that can be drawn is the enclosure management of pain in hospitalized dogs Animal Hospitals Prof Soeparwi better Jogja Animal Clinic. It would be nice if the development of the animal enclosures inpatient pain in Jogja Animal Clinic immediately resolved so that patients hospitalized dogs and cats can be immediately removed to prevent stress on the animal.